2022
DOI: 10.3390/cancers14020450
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial Infusion Chemotherapy in Advanced Pancreatic Cancer: A Comprehensive Review

Abstract: Advanced pancreatic cancer (PC) has a very poor prognosis due to its chemoresistant nature. Nowadays, only a few therapeutic options are available for PC, and the most effective ones are characterized by low response rates (RRs), short progression-free survival and overall survival, and severe toxicity. To improve clinical results, small series studies have evaluated loco-regional chemotherapy as a treatment option for PC, demonstrating its dose-dependent sensitivity towards the tumor. In fact, pancreatic arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…Typically, preoperative arteriography of the celiac artery and superior mesenteric artery (SMA) is performed to observe the blood supply of the tumor and to select the target vessel. [13] Tanaka et al [32] attempted embolization of the pancreatic artery originating from the SMA to achieve a single supply of the celiac artery to the tumor. This study found that SMA embolization can not only increase the regional drug concentration of the tumor, but also have an effect on liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, preoperative arteriography of the celiac artery and superior mesenteric artery (SMA) is performed to observe the blood supply of the tumor and to select the target vessel. [13] Tanaka et al [32] attempted embolization of the pancreatic artery originating from the SMA to achieve a single supply of the celiac artery to the tumor. This study found that SMA embolization can not only increase the regional drug concentration of the tumor, but also have an effect on liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The regional chemotherapy (RegCTx) approach is an oncological approach with a very low toxicity profile and high tumour response due to high cytotoxic drug concentrations in an isolated perfusion bed [ 13 , 14 , 15 , 16 , 17 , 18 ]. In addition, the therapy can be focused on limited regions if necessary, using the same technique, e.g., hypoxic abdominal stop-flow perfusion (HAP), upper abdominal perfusion (UAP), isolated thoracic perfusion (ITP) and intra-arterial infusion.…”
Section: Introductionmentioning
confidence: 99%
“…The restricted perfusion bed that is treated during RegCTx allows potentiation of drug concentration levels at the tumour site compared to sCTx, despite using up to 20–50% lower overall cytotoxic drug amount. Furthermore, the possibility to perform a chemo-filtration ensures the lowest systemic toxicity effects [ 12 , 13 , 14 , 16 , 18 ]. RegCTx efficacy has been proven in many cancers but has not been reported in advanced metastatic CCC.…”
Section: Introductionmentioning
confidence: 99%
“…The regional chemotherapy (RegCTx) approach is an oncological approach with very low toxicity profile and high tumor response due to high cytotoxic drug concentrations in an isolated perfusion bed [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In addition, the therapy can be focused on limited regions if necessary, using the same technique (e.g., upper abdominal perfusion (UAP), isolated thoracic perfusion (ITP), and intra-arterial infusion (AI)).…”
Section: Introductionmentioning
confidence: 99%
“…The restricted perfusion bed that is treated during RegCTx allows potentiation of drug concentration levels at the tumor site compared to sCTx despite using up to 20–50% of lower overall cytotoxic drug amount. Furthermore, the possibility to perform a chemo-filtration ensures lowest systemic toxicity effects [ 12 , 14 , 15 , 16 , 19 ]. RegCTx efficacy has been proven in many cancers including metastatic gastric cancer but has not been reported in advanced metastatic EC.…”
Section: Introductionmentioning
confidence: 99%